2019
DOI: 10.1386/jmte.12.1.25_1
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the ‘tyranny of distance’ in instrumental music tuition in Australia: The iMCM project

Abstract: Instrumental and vocal music students in regional and remote areas of Australia are often significantly disadvantaged in their development by the lack of local teachers who specialize in the instrument being learned. The current rollout of National Broadband Network (NBN) across Australia offers the potential for overcoming this geographical disadvantage by providing specialist online tuition through videoconferencing. This article reports on an investigation of technical and pedagogical issues associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Increased training, professional learning, and alignment between technologies and their application in teaching practice are needed. As noted by Stevens (2018), the use of ICT in music education has been "taken for granted" (p. 59) for many years. Bauer and Dammers (2016) identified that preservice music teachers "are not being engaged in experiences that will assist them in understanding pedagogical approaches for using the technologies in music teaching" (p. 9).…”
Section: Music Technology and Ict: Teacher Training And Professional ...mentioning
confidence: 99%
“…Increased training, professional learning, and alignment between technologies and their application in teaching practice are needed. As noted by Stevens (2018), the use of ICT in music education has been "taken for granted" (p. 59) for many years. Bauer and Dammers (2016) identified that preservice music teachers "are not being engaged in experiences that will assist them in understanding pedagogical approaches for using the technologies in music teaching" (p. 9).…”
Section: Music Technology and Ict: Teacher Training And Professional ...mentioning
confidence: 99%
“…Research in this area generally focuses on how music education can be made more accessible to regional and remote communities (e.g., Crawford, 2017). Such studies also tend to discuss instrumental music tuition rather than general music classes (e.g., King et al, 2019aKing et al, , 2019bStevens et al, 2019). However, within the context of higher education, there is a considerable amount of literature exploring online learning for music courses (e.g., Blackburn, 2017;Johnson, 2017a;Johnson & Lamothe, 2018), which is unsurprising considering the significant number of American universities offering distance learning in this area (Blake, 2018;Johnson, 2017b).…”
mentioning
confidence: 99%